Codicological Patterns And Regional Variation On Islamic Manuscripts In Sumatra - Roma Kyo Kae Saniro; Ahmad Hamidi (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2026)
The Islamic books of Sumatra provide primary evidence for mapping the material heritage, intellectual history and social transmission of Islam in Southeast Asia. While these manuscripts are frequently noted as significant, textual work has advanced much more thoroughly than the codicology of such objects This study examines the codicological features of Islamic manuscripts in Sumatra and identifies regional variations and local adaptations in relation to textual functions and social uses. This study employs a qualitative descriptive-analytical method using a codicological approach. The data consist of codicological descriptions of Islamic manuscripts from various regions in Sumatra, including information on manuscript materials, script types, ink colors, page layout, orientation, dimensions, and physical characteristics. The data were compared and analyzed thematically to identify similarities and differences among manuscripts from different regions. The findings show that Islamic manuscripts in Sumatra share several codicological features, including the widespread use of European paper and Arabic-based scripts, while regional differences reflect local adaptations and specific social functions. The analysis also shows that codicological features are closely related to textual genres and patterns of manuscript use. Ultimately, a codicological reading of Islamic manuscripts not only provides an important way of reading these documents as socio-historical artefacts but also supports philology by embedding texts within their materiality and culture.   Manuskrip Islam dari Sumatra merupakan sumber penting untuk memahami budaya material, sejarah intelektual, dan transmisi sosial Islam di Asia Tenggara. Meskipun penting, studi tentang manuskrip ini sebagian besar berfokus pada konten tekstual, sementara aspek kodikologis kurang mendapat perhatian sistematis. Studi ini bertujuan untuk menganalisis unsur-unsur kodikologis manuskrip Islam di Sumatra guna mengidentifikasi pola regional, variasi lokal, dan hubungannya dengan fungsi tekstual dan penggunaan sosial. Metode deskriptif-analitis kualitatif dengan analisis kodikologis digunakan pada penelitian ini. Data dikumpulkan melalui pemeriksaan komparatif manuskrip Islam yang terdokumentasi dari beberapa wilayah di Sumatra, dengan fokus pada bahan tulis, aksara, tata letak halaman, tinta, ukuran manuskrip, dan kondisi fisik. Analisis data dilakukan secara tematik untuk memeroleh persamaan dan perbedaan antarwilayah. Temuan menunjukkan bahwa manuskrip Islam di Sumatra memiliki ciri-ciri kodikologis yang sama, seperti penggunaan dominan kertas Eropa dan aksara berbasis Arab, yang menunjukkan integrasi ke dalam jaringan Islam yang lebih luas. Pada saat yang sama, variasi regional dalam media, tata letak, dan aksara mencerminkan adaptasi lokal dan fungsi sosial yang berbeda. Studi ini juga menunjukkan hubungan erat antara bentuk kodikologis, genre tekstual, dan pola penggunaan. Kesimpulannya, pendekatan kodikologis memberikan wawasan kritis terhadap manuskrip Islam di Sumatra sebagai artefak sosial dan memperkuat penelitian filologis dengan menempatkan teks dalam konteks material dan budayanya.